PENGAYAAN KOMPOS JERAMI PADI DENGAN BUBUK BATU SEBAGAI SUMBER HARA UNTUK TANAMAN SAWI (Brassica juncea L.) PADA PERTANIAN ORGANIK - Santaliana Br Tarigan; Bintang Sitorus; Hamidah Hanum (Universitas Sumatera Utara, 2012)
ABSTRACT Enrichment of rice straw with rock powder as biofertilizer to supply nutrient for a vegetable (Brassica juncea L) to organic agricultural. The aim of this research is to determine the potention enrichment of rice straw with rock powder as biofertilizer to supply N,P,K nutrient for a vegetable (Brassica juncea L) to organic agricultural. This study used a Randomized Blok Design with ten treatments and three replications. The treatment consists of OO (control), KJ (aplication of compost without enrichment), KD (aplication of compost enrichment by 175 g dolomite), KP (aplication of compost enrichment by 175 phosphate ), KZ (aplication of compost enrichment by 175 g zeolite), KS (aplication of compost enrichment by 175 g river’s rock), KD1 (aplication of compost enrichment by 350 g dolomite), KP1 (aplication of compost enrichment by 350 g phosphate), KZ1 (aplication of compost enrichment by 350 g zeolite), KS1 (aplication of compost enrichment by 350 g river’s rock). The results showed that administration of rice straw compost which increase with rock powder after incubation significantly increased pH of soil, N soil, and K- exchange at treatment of compost that increase with dolomite docage 350 g and P-available at treatment of compost that increase with fosfate docage 350 g. Compost of straw rice which increace with rock powder significantly increased of vegetable growth at treatment of compost that increase with fosfate docage 350 g. Keywords : compost of straw rice, rock powder, vegetable (Brassica juncea L) ABSTRAK Pengayaan kompos jerami padi dengan bubuk batu sebagai sumber hara untuk tanaman sawi (Brassica juncea L.) pada pertanian organik. Penelitian ini bertujuan untuk mengetahui potensi kompos jerami padi yang diperkaya dengan tepung batu sebagai pupuk alami dalam menyediakan hara N, P, K untuk tanaman sawi (Brassica juncea L.) pada pertanian organik. Penelitian ini menggunakan Rancangan Acak Lengkap dimana perlakuan terdiri atas OO (Kontrol), KJ (50 g aplikasi kompos tanpa diperkaya), KD (aplikasi kompos diperkaya 175 g dolomit), KP (aplikasi kompos diperkaya 175 fosfat ), KZ (aplikasi kompos diperkaya 175 g zeolit), KS (aplikasi kompos diperkaya 175 g batu sungai), KD1 (aplikasi kompos diperkaya 350 g dolomit), KP1 (aplikasi kompos diperkaya 350 g fosfat), KZ1 (aplikasi kompos diperkaya 350 g zeolit), KS1 (aplikasi kompos diperkaya 350 g batu sungai). Hasil penelitian menunjukkan bahwa pemberian kompos jerami padi yang diperkaya tepung batu setelah inkubasi nyata meningkatkan pH tanah, N-total, K-tersedia pada perlakuan aplikasi kompos diperkaya dolomit dosis 350 g dan P-tersedia pada perlakuan kompos diperkaya fosfat dosis 350 g. Pemberian kompos jerami padi yang diperkaya tepung batu nyata dalam meningkatkan pertumbuhan tanaman sawi pada perlakuan kompos diperkaya fosfat dosis 350 g. Kata kunci: kompos jerami padi, tepung batu, sawi (Brassica juncea L).